Clinicopathological Spectrum and Prevalence of Cutaneous Carcinomas: Experience from a Single Institution - Faiza Fatima, Saima Gulzar, Koukab Gulzar, Sehrish Ashraf (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Cutaneous carcinomas are relatively uncommon in the Asian population but nonetheless consist of a significant proportion of carcinomas .Early diagnosis is required to avoid destructive surgeries and potential disfiguring which is both psychologically and physically detrimental for patients. Basal cell carcinoma and squamous cell carcinoma encompass most of the cases of cutaneous carcinomas in Asian populations such as those living in Pakistan. Objectives: To determine the frequency, clinical features, and morphological spectrum of cutaneous carcinomas in patients presented to Services Hospital Lahore. Methodology: It is a retrospective cohort study conducted at Services Hospital Lahore from 1st January 2014 to 31st December 2022 and comprised 100 cases. Results: The ratio of male to female was 1:1.3 and the mean age of presentation was 56.42 years. Basal cell carcinoma (76%) was the most frequent occurrence followed by squamous cell carcinoma (24%). The nose was the most common site of presentation (13%) followed by the cheek (11%). The Nodular histological subtype was most common (37%) followed by basosquamous (15%). Sun exposure was the most common etiological factor with the least common being genetic disorders including xeroderma pigmentosa 3%. Grade 1 tumors were the most common (58%). Conclusion: Nodular basal cell carcinoma was the most prevalent subtype of basal cell carcinoma, while keratinising type was the most common subtype of squamous cell carcinoma. The average age of presentation was 56.42 years. Keywords: Basal cell carcinoma, Squamous cell carcinoma, Morphological spectrum, Clinical features